Processamento sensorial e engajamento de crianças nas rotinas da educação infantil na perspectiva dos professores - Barros, Vanessa de Melo (2019)
The engagement is essential for successful development. Sensory processing skills promote commitment. However, the relationship between sensory processing skills and commitment of children in the school routine is little studied in Brazil. The study identified the correlations between patterns of sensory processing and engagement in routines of children in childhood education with typical development. It is a descriptive, correlational study. This study involved 9 educators linked to the 5 municipal schools, as well as 70 children of 3 years and typical development, enrolled full-time in early childhood education. The evaluation instruments used were Sensory Processing Measure-Preschool - SPM-P and the Classroom Measure of Engagement, Independence, and Social Relationships - ClaMEISR. The data collection was carried out by filling out the questionnaires by the teachers, under the supervision of the researcher. For the analysis of the data, descriptive statistical analyzes and the statistical software package for the verification of correlations were used. The study showed that 73% of children have a typical pattern of sensory processing in relation to reactivity and modulation, although in all the sensory systems addressed by the questionnaire used; children with slight to definitive dysfunctions were identified, with the auditory system being, visual and vestibular, those with the highest incidence. For planning and ideation, 63% of the children presented typical performance and for social relations 48% of the children did not present sensory dysfunction. Regarding engagement, for that study the questionnaire left doubts regarding the analysis of its score. Therefore, percentages were established that classified the children into 3 levels, sophisticated engagement 27% of the children, uncomplicated or differentiated engagement 46% and not the engagement of 27% of the total of children evaluated. From these results and statistical analysis it was possible to observe mild and moderate correlations in all the categories presented by the questionnaires, with scores equal to or higher than 0.5. From these correlations, the music, park, meal, small group and free play routines showed a greater correlation with the sensory processing variables, especially social participation, body awareness, which refers to the proprioceptive system, planning and ideation, referring to praxis and total modulation value. Thus, the study points to an important contribution of the typical performance of sensory processing to the sophisticated engagement in school routines. Considering that in school the child is expected to engage in his or her routines for good performance, and that the occupational therapist has dedicated his studies to understand the engagement and patterns of sensory processing, the study emphasizes that the approach of this professional with educators and children can minimize possible deficits presented by children. This partnership can further potentiate the school environment so that the child remains largely time sensory organized and in an environment with suitable possibility for sophisticated engagement.